SHARIA FINANCIAL SERVICES COOPERATIVE IN REVIEW OF FIQH MUAMALAH - Rahima Kumala (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
Microfinance institutions as one of the pillars of the Indonesian economy by providing financing to small businesses are expected to help in alleviating poverty in Indonesia. One of them is the Sharia Financial Services Cooperative (KJKS) which has sharia-based operational standards. This study aims to see how the KJKS in the Fiqh Muamalah Review. This study uses a literature study method by mapping the themes of previous studies. Search articles using the Google Scholar database with the keywords “fiqh muamalah” OR “fiqh muamalah” OR “fiqh muamalah” AND “sharia financial services cooperatives”. In the period 2017 to 2022, 61 articles were found which were then selected into 37 articles that were considered still relevant to the themes discussed. Of the 37 selected articles, they have been grouped into several themes: 1) Contracts in Islamic cooperatives 2) Sharia Cooperative Services 3) Supervision and Risk Management of Sharia Cooperatives 4) Conformity of the Concept and Relevance of Fiqh Muamalah in Financing Practices 5) Performance of DPS in Sharia Cooperatives. The results of this study are in principle KJKS has carried out operational activities by Fiqh Muamalah, operational activities based on sharia law, regarding human behavior in their lives which are obtained from Islamic arguments in detail. Operational activities of Sharia Financial Services Cooperatives or BMTs are supervised by the Financial Services Authority (OJK), Sharia Supervisory Board (DPS), and the Ministry of Cooperatives and SMEs in each of its activities, however, there are still KJSK that carry out operational activities that are not by fiqh muamalah, this is due to a lack of understanding. concerning fiqh muamalah in the activities of the Sharia Financial Services Cooperative.